PRELIMINARY ABUNDANCE ANALYSIS OF 9 SUBDWARFS - Mishenina, T. V.; Gorbaneva, T. I.; Kantsen, L. E. (Одеські астрономічні публікації, 2017)
We provide parameter and abundance determination of 9 subwarfs including two SMR stars (HD 161797 and HD 182572). These stars show metallicity overabundance in agreement with previous results. Further we plan to carry out the detailed analysis of luminosity, evolutionary status, age and belonging of studied stars to spatial structures of the Galaxy.